Infidelidad y su influencia en el desarrollo emocional de un adolescente del Sector el Mirador de la Parroquia 10 de Noviembre, cantón Ventanas, Provincia de Los Ríos - Rodriguez Flores, Karla Lissette (2020)
The present study aims to contribute to the problem that is occurring in the El Mirador Sector, the purpose of which is to describe the influence of infidelity on the emotional development of an adolescent. The study was carried out in an adolescent from the EL Mirador sector of the November 10 parish of the Ventana’s canton, Los Ríos province, applying a reagent and a survey, in such a way that the analysis and interpretation of the results establishes that marital infidelity It intervenes significantly in the adequate emotional development of patients, which allows to consider conclusions and recommendations.